How to not mesh it up? : Discovering Critical Success Factors for Data Mesh project - Willems, Pieter (My University, 2022)
Organizations are constantly looking for ways to improve their business success or competitive position. To achieve this goal organizations need to become data-driven. Current data architectures are seen by some as not future-proof. However, Data mesh is an example of a data architecture that is future-proof. Implementing new innovations such as data mesh is a challenge for most organizations The aim of this research is to discover critical success factors for a data mesh project, to ensure that organizations can implement data mesh more efficiently. The research strategy to achieve this goal is grounded theory. To discover the critical success factors for data mesh, grounded theory research was conducted, by doing a single case study. The case study consisted of two separate rounds of interviews. The interviewees of the first round were used to gather data. The second round was designed to interpret the results and selected the critical success factors through validation interviews. The results showed that the definition of a successful data mesh implementation varies across organizations. The findings identify six critical success factors, such as data quality, showing value, clear roles and responsibilities, project champion, and alignment between domains, which managers should focus on when implementing data mesh. It was found that there are additional factors needed to help a large enterprise implement data mesh, and these factors are defined as well. The main conclusion drawn from this research is that the collective application of the factors is needed, rather than applying each factor individually.
Keywords: Data Mesh, Critical Success Factors, Project Success, IT failure, IT Projects